Current Smoking Status Is Associated With Lower Quantitative CT Measures of Emphysema and Gas Trapping. Issue 1 (January 2016) - Zach, Jordan A.; Williams, Andre; Jou, Sung-Shiick; Yagihashi, Kunihiro; Everett, Douglas; Hokanson, John E.; Stinson, Douglas; Lynch, David A.
Abstract : Purpose: The purposes of this study were to evaluate the effect of smoking status on quantitative computed tomography CT measures of low-attenuation areas (LAAs) on inspiratory and expiratory CT and to provide a method of adjusting for this effect. Materials and Methods: A total of 6762 current and former smokers underwent spirometry and volumetric inspiratory and expiratory CT. Quantitative CT analysis was completed using open-source 3D Slicer software. LAAs were defined as lung voxels with attenuation values ⩽−950 Hounsfield units (HU) on inspiratory CT and ⩽−856 HU on expiratory CT and were expressed as percentage of CT lung volume (%LAAI-950 and %LAAE-856 ). Multiple linear regression was used to determine the effect of smoking status on %LAAI-950 and %LAAE-856 while controlling for demographic variables, spirometric lung function, and smoking history, as well as total lung capacity (%LAAI-950 ) or functional residual capacity (%LAAE-856 ). Quantile normalization was used to align the %LAAI-950 distributions for current and former smokers. Results: Mean %LAAI-950 was 4.2±7.1 in current smokers and 7.7±9.7 in former smokers ( P <0.001). After adjusting for confounders, %LAAI-950 was 3.5 percentage points lower and %LAAE-856 was 6.0 percentage points lower in current smokers than in former smokers ( P <0.001). After quantile normalization, smoking status was an insignificant variable in the inspiratory regression model, with %LAAI-950 being 0.27 percentage points higher in current smokers ( P =0.13). Conclusions: After adjusting for patient demographics and lung function, current smokers display significantly lower %LAAI-950 and %LAAE-856 than do former smokers. Potential methods for adjusting for this effect would include adding a fixed value (eg, 3.5%) to the calculated percentage of emphysema in current smokers, or quantile normalization. Abstract : Supplemental Digital Content is available in the text.